2014
DOI: 10.1002/jcb.24709
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis Regulation at the Mitochondrial Outer Membrane

Abstract: Mitochondria play a critical role in apoptosis, or programmed cell death, by releasing apoptogenic factors from the intermembrane space. This process, known as mitochondrial outer membrane permeabilization (MOMP), is tightly regulated by the Bcl-2 family proteins. Pro-apoptotic Bcl-2 family members, Bax and Bak, change their conformation when activated by BH3 domain-only proteins in the family and permeabilize the MOM, whereas pro-survival members inhibit permeabilization. The precise nature of the apoptotic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
125
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(134 citation statements)
references
References 108 publications
3
125
0
2
Order By: Relevance
“…The balance between Bcl-2 and Bax is critical in the activation of terminal caspases such as caspase-9 and caspase-3 [19]. Treatment of PC12 cells with OGD/R significantly decreased protein levels of Bcl-2 and increased protein levels of Bax compared with the control group, which resulted in a low ratio of Bcl-2/ Bax (P < 0.05 vs. control) (Fig.…”
Section: Resveratrol Inhibited Ogd/r-induced Cytochrome C Release Fromentioning
confidence: 89%
“…The balance between Bcl-2 and Bax is critical in the activation of terminal caspases such as caspase-9 and caspase-3 [19]. Treatment of PC12 cells with OGD/R significantly decreased protein levels of Bcl-2 and increased protein levels of Bax compared with the control group, which resulted in a low ratio of Bcl-2/ Bax (P < 0.05 vs. control) (Fig.…”
Section: Resveratrol Inhibited Ogd/r-induced Cytochrome C Release Fromentioning
confidence: 89%
“…Therefore, mitochondria are important therapeutic targets for ischemic cerebral stroke (Chan, 2005). Among numerous mitochondrial proteins, Bcl-2 family including Bcl-2, Bcl-XL, Mcl-1, Bax, Bak, Bcl-XS, Bad, Bik and Bid are central regulators of mitochondria-dependent programmed cell death (Graham et al, 2000;Antonsson, 2001;Youle and Strasser, 2008;Gillies and Kuwana, 2014). Bcl-2 is an integral membrane protein located mainly on the outer membrane of mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, increases in the mRNA levels of Bcl-2 and Hspa4 were identified in hippocampal NSCs following treatment with 20 µM selegiline for 48 h. The Bcl-2 protein family controls the release of cytochrome c (Cyt-c) from the mitochondria and consists of pro-apoptotic (Bcl-2-associated X protein, Bcl-2 homologous antagonist/killer, BH3 interacting-domain death agonist, Bcl-2-associated death promoter) and anti-apoptotic [Bcl-2, Bcl-extra large (Bcl-xL)] members (34). The primary function of anti-apoptotic Bcl-2 is to suppress mitochondrial Cyt-c release, by regulating physiological membrane permeability, Ca 2+ release and oxidative stress in the mitochondria (35,36).…”
Section: Discussionmentioning
confidence: 99%